Plan de comercialización de insumos de bioseguridad veterinarios para la empresa IVETMAS de la ciudad de Cuenca - Pintado Morales, Edwin Oswaldo (2025)
This degree project developed a marketing plan for IVETMAS veterinary biosecurity supplies in Cuenca city, specifically in Cumbe parish, with the aim of strengthening the company's market positioning, this study aimed to create a marketing plan to enhance IVETMAS’s positioning in Cumbe, where the brand was not widely recognized among local producers. To address this, a mixed-method market study was conducted, utilizing surveys with producers and distributors, interviews with key stakeholders, and direct observation. The results showed that 70% of respondents were unfamiliar with the IVETMAS brand, highlighting the need for marketing and digital commercialization strategies. The study also identified that hygiene and disinfection products accounted for 63% of demand, presenting an opportunity to strengthen this product line through targeted marketing and added-value strategies. Additionally, social media (40.7%) and traditional media advertising (22.2%) were identified as the primary sources of information about the company’s products.The study concluded that a structured marketing plan would allow IVETMAS to consolidate its brand image, improve market segmentation, and increase its competitiveness in the agro-industrial sector. It was recommended to enhance the company’s digital presence, optimize after-sales services, implement customer loyalty strategies, and expand the distribution network. The adoption of these actions would contribute to the company’s sustainable growth and promote the implementation of biosecurity practices in agricultural production.